Entrepreneurial mindset: Dispositional beliefs, opportunity beliefs, and entrepreneurial behavior. (2nd January 2023) - Pidduck, Robert J.; Clark, Daniel R.; Lumpkin, G. T.
ABSTRACT: Research on entrepreneurial mindset (EM) has proliferated in recent years. Its importance rests on a key assumption: EM matters for entrepreneurial behavior. However, to date, EM conceptualizations remain fragmented, and theories delineating the relationship between EM and the behaviors underpinning entrepreneurship are limited. In this article, we conceptualize EM as a goal orientation formed through dispositional beliefs about entrepreneurship and opportunity beliefs, which results in entrepreneurial behaviors. We draw upon recent advances in entrepreneurial orientation (EO) research at the individual level as a model for dispositional beliefs. Further, we theorize the origins, mechanisms, manifestations, and effect of EM. Finally, we discuss important implications for stakeholders interested in leveraging EM to stimulate entrepreneurial activity and lay out a research agenda for future development of our disposition-based framework.